1986
DOI: 10.2337/diacare.9.5.472
|View full text |Cite
|
Sign up to set email alerts
|

Children's Self-Reports of Psychologic Adjustment and Coping Strategies During First Year of Insulin-Dependent Diabetes Mellitus

Abstract: Psychologic adjustment, assessed by self-ratings of anxiety, self-esteem, and depression, and cognitive as well as behavioral coping strategies, elicited by interview, were monitored longitudinally among school-age children with recent-onset insulin-dependent diabetes mellitus (IDDM). Our article documents the findings over the 1st yr of illness. From the start, the children viewed themselves as self-confident and emotionally comfortable. The diagnosis of IDDM created minimal emotional upheaval (which faded wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 7 publications
2
60
1
2
Order By: Relevance
“…This difference arose from lower scores on the psychosocial subscale, which assessed parental perception of the child's adjustment at school and level of social and emotional functioning. Other investigators have also reported that while children with diabetes generally do not have severe psychological problems (24,25); when they do struggle, it is often in the socialemotional and peer relationship areas of functioning (26,27). Nonetheless, the remarkable similarity in general quality of life between youth with type 1 diabetes and a healthy sample contrasts with a recent report of quality of life from 106 severely obese youth (28).…”
Section: Stability Of Child and Parent Proxy Reports Over 1 Yearcontrasting
confidence: 49%
“…This difference arose from lower scores on the psychosocial subscale, which assessed parental perception of the child's adjustment at school and level of social and emotional functioning. Other investigators have also reported that while children with diabetes generally do not have severe psychological problems (24,25); when they do struggle, it is often in the socialemotional and peer relationship areas of functioning (26,27). Nonetheless, the remarkable similarity in general quality of life between youth with type 1 diabetes and a healthy sample contrasts with a recent report of quality of life from 106 severely obese youth (28).…”
Section: Stability Of Child and Parent Proxy Reports Over 1 Yearcontrasting
confidence: 49%
“…This study, as well as others, subsequently found that by 1 year after diagnosis, symptoms resolved in the majority of children as well as their parents, suggesting that successful psychosocial adjustment occurs relatively quickly in most families (Jacobson et al, 1986;Kovacs et al, 1986). These positive findings were somewhat tempered by subsequent research that showed that psychosocial problems often re-emerge in youths several years after diagnosis and that difficulty in coping with diabetes can increase over time (Grey, Cameron, Lipman, & Thurber, 1995), especially in those patients who exhibit poor initial adjustment (Kovacs et al, 1986). Unfortunately, there have been no such longitudinal studies of psychosocial adjustment in adults, even though clinicians are frequently faced with the problem of "diabetes burnout," which is common in patients who have been dealing with the disease for a number of years (Polonsky, 1999).…”
Section: Psychosocial Adjustment and Qolmentioning
confidence: 92%
“…Other studies reported that children with type 1 DM generally did not have serious psychosocial problems and that the problems seen were related to emotional, social, and peer relationships (25,26,27). A descriptive crosssectional study of the economic situation involving three hundred diabetic patients showed that the social class had significant effects on quality of life and compliance with treatment (28).…”
Section: Discussionmentioning
confidence: 99%